2010
DOI: 10.1002/nme.2878
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐time‐step domain coupling method with energy control

Abstract: SUMMARYA multi-time-step integration method is proposed for solving structural dynamics problems on multiple domains. The method generalizes earlier state-space integration algorithms by introducing displacement constraints via Lagrange multipliers, representing the time-integrated constraint forces over the individual time step. It is demonstrated that displacement continuity between the subdomains leads to cancelation of the interface contributions to the energy balance equation, and thus stability and algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Figure 19 provides a pictorial description of the problem. A similar problem is also considered in Reference [22], which also addressed multi-time-step coupling method for structural dynamics.…”
Section: Representative Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 19 provides a pictorial description of the problem. A similar problem is also considered in Reference [22], which also addressed multi-time-step coupling method for structural dynamics.…”
Section: Representative Numerical Resultsmentioning
confidence: 99%
“…Real time partitioned time-integration using the LSRT methods has been of interest recently in [21]. Mahjoubi and Krenk proposed a multi-time-step coupling method using state-pace time integration in [22], a more general presentation of which appears in [23]. Another work that is relevant to the current paper is by Prakash and Hjelmstad [24], which we shall refer to as the PH method.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the PH method is energy conserving when coupling non‐dissipative Newmark schemes such as the implicit constant average acceleration (CAA) scheme and the explicit central difference (CD) scheme. Recently, the Mahjoubi Gravouil Combescure (MGC) method (based on a similar macro timescale velocity continuity assumption) has been built in order to be able to couple the Newmark schemes, HHT‐ α scheme , Simo scheme , and Krenk scheme (balance dissipation scheme, ) in linear dynamics . In other words, the MGC method can be seen as an extension of the PH method to the HHT‐ α scheme.…”
Section: Heterogeneous Asynchronous Time Integratorsmentioning
confidence: 99%
“…As shown in [12], the normal contact conditions (37) in combination with the trapezoidal rule yield an unstable algorithm if inertia terms are present. In this case, it is advisable to change the time discretization of (37) like, e.g., described in [27,55].…”
Section: Frictional Contactmentioning
confidence: 99%
“…In [34,35], a time sub stepping scheme with linear interpolation of the velocity and the Lagrange multipliers has been proposed which is stable but dissi pative at the interface. An improved energy conserving scheme with linear interpolation of the multipliers has been analyzed in [36,37]. However, both methods rely on the expensive exact solu tion of the resulting coupled system.…”
Section: Introductionmentioning
confidence: 99%